[tex](\stackrel{x_1}{2}~,~\stackrel{y_1}{21})\qquad (\stackrel{x_2}{4}~,~\stackrel{y_2}{42}) ~\hfill \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{42}-\stackrel{y1}{21}}}{\underset{run} {\underset{x_2}{4}-\underset{x_1}{2}}}\implies \cfrac{21}{2}[/tex]
[tex]\begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{21}=\stackrel{m}{\cfrac{21}{2}}(x-\stackrel{x_1}{2}) \\\\\\ y-21=\cfrac{21}{2}x-21\implies y=\cfrac{21}{2}x[/tex]